As Quiet As Night, As Cheerful As Day : Case-Solving Patterns in Enola Holmes (2020) and Sherlock Holmes (2009) Films and the Influence of Color on the Case - Nazwa Maritzsa Wahyudin; Hasbi Assidiqi; Dian Nurrachman (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Enola Holmes and Sherlock Holmes produce different shows within the same genre. This research aims to discover the differences in case-solving techniques between Enola and Sherlock Holmes. The appropriate method for this research is qualitative using literary criticism. The researcher only focused on the films and reference sources to find out the case-solving patterns and the influence of color in Enola Holmes and Sherlock Holmes. The findings are that Enola uses more case-solving techniques, such as wordplay and intuition, and prioritizes feelings. The colors displayed also look more cheerful with a combination of bright colors. Whereas, Sherlock uses more deductive abilities with a focus on goals without involving his feelings by using dark colors that make him look serious and dark. In his every action, there is no hesitation at all. This research proves the difference between Sherlock and Enola in solving cases and the fact that colors are not just aesthetics but can also support the narrative, which then creates a deeper message and atmosphere.